Motivation for adherence to antiretroviral therapy by transgender people living with hiv - A study in West Bengal, India - Gautam Kumar Ghosh; Subrata Biswas; Piyali Ghosh; Suman Ganguly; Malay Kumar Saha (Wolters Kluwer Medknow Publications, 2020)
The introduction of antiretroviral therapy (ART) has substantially improved the survival of persons infected with HIV. In India, the aggregated HIV prevalence among transgender (TG) community was found 7.5%. West Bengal, with over 30,000 TG population recorded HIV prevalence of 4.8%. The qualitative study was conducted in 2019 with the objective to explore the motivating factors for adherence to ART treatment among TG people living with HIV (PLHIV) in an ART center. Respondents were motivated PLHIVs on ART with suitable treatment adherence recorded. Data were inductively analyzed, using thematic analysis, to identify themes central to ART adherence. Five themes emerged with prime acknowledgment of respondents that ART medication is lifelong for their survival with receiving support. Notwithstanding the chronic nature of the disease, TG PLHIV patient stands a better chance of maintaining treatment adherence if they are involved in treatment plans with their community-based members' helping as peer navigators.